The Effect of Capital Employed, Human Capital and Structural Capital on Financial Performance on the Consumer Goods Sector Period 2015-2019 - Yerisma Welly; Arfan Ikhsan; Chandra Situmeang (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2021)
This study aims to examine the effect of Capital Employed Efficiency (CEE), Human Capital Efficiency (HCE) and Structural Capital Efficiency (SCE) on the financial performance of Return On Equity (ROE) of companies in the consumer goods industry sector. The population in this study is the financial statements of companies in the consumer goods industry listed on the IDX during the 2015-2019 period. This study used purposive sampling with 31 companies and 155 observations. The method of data analysis in this study is panel data regression with a panel that is more appropriate to use is the Fixed Effect Model (FEM) method using the Eviews 9 program as a data processing program. The results showed that CEE and SCE had a positive and significant effect on financial performance. If the higher the CEE and SCE, the higher the ROE of the company, so this can create stakeholder trust in the company. Meanwhile, employee costs are costs that have relatively no effect on income, while ROE is indicated by income, thus proving that HCE has a positive effect, but does not have a significant effect on financial performance.